The Ontological Metaphor In Mambere Tungkot, Duda-Duda, And Sulang-Sulang Pahompu In Batak Simalungunese Tradition In North Sumatra Indonesia - Girsang, Martina; Silalahi, Charles David Marudut; Sembiring, Elita Modesta Br; Sianturi, Srisofian (Lembaga Penelitian dan Pendidikan Mandala, 2021)
This paper describes and analyzes the ontological metaphor language in a traditional Batak Simalungunese tribe, Mambere Tungkot, Duda-Duda, and Sulang-Sulang Pahompu in North Sumatra, Indonesia. This study aims to present an analytical view of the customary tradition of thanking parents for their contribution to one’s life. This is carried out in regular conversation through the language of metaphors, in particular, ontology metaphors. Ontological metaphors describe human qualities that are given to nonhuman entities (Kovesces, 2010: 33-38). This study applies the descriptive qualitative method to discuss the ontological metaphor depicted in the traditional ceremony. The data of the research were taken from the utterances of the speakers, namely: master of the ceremony, parents, and children involved in the ceremony. The concept of this study is the communication theory in the context of the ontological metaphor to analyze the data. The result of the study shows that most of the utterances in the traditional ceremony use ontological metaphors.